WikiRevolution? - Der Derian, James (Politik, 2012)
Did WikiLeaks change the world? Lost in the sensationalism, personalization and media spasm of the event was any historical or political assessment of how or even whether the revelation of state secrets actually a ects the conduct of diplomacy and war. Taking one step back, two steps forward, this essay compares historic whistle blowing – like Trotsky’s opening of the Tsarist diplomatic archives after the Russian revolution and Wilson’s call for a transparent new diplomacy after the First World War – to the polarized reaction that fol- lowed the passing of over a half million classi ed documents and two videos by Private Bradley Manning to WikiLeaks. e signi cance of the event should be judged less by the content of the documents and more by the emergence of a new networked medium of global transmission that further erodes the institutions and prerogatives of statecraft.